2014
DOI: 10.1016/j.pop.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute Otitis Media

Abstract: One in 4 children will have at least 1 episode of acute otitis media (AOM) by age 10 years. AOM results from infection of fluid that has become trapped in the middle ear. The bacteria that most often cause AOM are Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. Differentiating AOM from otitis media with effusion (OME) is a critical skill for physicians, as accurate diagnosis will guide appropriate treatment of these conditions. Although fluid is present in the middle ear in both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
3
17
0
2
Order By: Relevance
“…AOM constitutes the prime indication for antibiotic prescription in infants,20 21 hence pneumococcal vaccination by reducing the number of AOM cases could play a role in limiting the development of antibiotic resistance. In a cluster-randomised, double-blind trial, Palmu et al 80 reported that the use of PHiD-CV vaccine in Finland could result in yearly 12 000 fewer outpatient antibiotic purchases for AOM in children aged <2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AOM constitutes the prime indication for antibiotic prescription in infants,20 21 hence pneumococcal vaccination by reducing the number of AOM cases could play a role in limiting the development of antibiotic resistance. In a cluster-randomised, double-blind trial, Palmu et al 80 reported that the use of PHiD-CV vaccine in Finland could result in yearly 12 000 fewer outpatient antibiotic purchases for AOM in children aged <2 years.…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, in contrast to PCV-7 and PCV-13, PHiD-CV has the additional potential to target NT Hi -related AOM, due to the employment of protein D derived from NT Hi as a carrier protein for the majority of its conjugates 1819 This is important, as AOM represents a major indication for the prescription of antibiotics in infants 2021 Significant antibiotic resistance has been observed in Sp 22–24 and NT Hi bacteria,25 and the increasing resistance to antibiotics is globally recognised as a health policy concern.…”
Section: Introductionmentioning
confidence: 99%
“…Otitis media (OM) refers to a group of complex infectious and inflammatory diseases affecting the middle ear (Dickson, 2014). OM in general is very common, as studies show that around 80 % of children should have experienced at least one episode by their third birthday (Teele et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The main predisposing factors are local trauma and exposure of the skin to water. Diagnosis is made using typical history and direct observations of the ear canal, which presents with diffusely swollen, extremely tender, and shiny skin . The treatment involves avoiding the causative agent and empirical use of topical antibiotics, with ciprofloxacin being the first choice.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that AOE is associated with bacterial proliferation in the ear canal . As the suction system continuously removes exudate, it is speculated that the NPWT may promote bacterial clearance and control its proliferation in the wound bed .…”
Section: Discussionmentioning
confidence: 99%